COPD in a Construction Worker with Heavy Smoking History: Application of the PERDOKI Seven-Step Work-Relatedness Assessment - Noer Triyanto Rusli; Ardi Artanto (Fakultas Kedokteran Universitas Sriwijaya, 2026)
Chronic obstructive pulmonary disease (COPD) is a multifactorial disease in which tobacco smoking remains the dominant risk factor, while occupational exposure to vapours, gases, dusts, and fumes may contribute to disease development and progression. This case report describes a 65-year-old male construction labourer with a 48-pack-year smoking history and more than 30 years of unprotected occupational exposure to cement dust, sand, road dust, and probable respirable crystalline silica. He presented with worsening dyspnea and a productive cough consistent with an acute exacerbation of COPD. Spirometry showed airflow obstruction with FEV1/FVC of 59% and FEV1 of 60% predicted, corresponding to GOLD 2 airflow obstruction if confirmed by post-bronchodilator spirometry. Chest radiography demonstrated emphysematous changes, including bilateral hyperinflation, flattened diaphragms, attenuated vascular markings, and a vertical cardiac silhouette. Using the seven-step work-relatedness assessment of the Indonesian Association of Occupational Medicine Specialists (PERDOKI), occupational exposure was interpreted as a possible contributing factor rather than a definitive or sole cause, given the patient’s substantial smoking history and the absence of quantitative exposure monitoring. Management combined guideline-based COPD pharmacotherapy, smoking abstinence, workplace exposure reduction, respiratory protection, work modification, pulmonary rehabilitation referral, and periodic occupational health surveillance. This case highlights the importance of systematic occupational history taking in COPD patients, especially among construction workers with dual exposure to smoking and mineral dust.